Etika Profesi Notaris sebagai Penjaga Keamanan Hukum dalam Transaksi Bisnis - M. Nabih Royani; Ana Silviana (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Notaries play a crucial role in ensuring legal certainty and security in business transactions, especially in the creation of authentic deeds that serve as valid evidence and possess high legal force. As public officials authorized by the state, notaries are tasked with ensuring that every transaction involving the parties concerned is legally valid, fair, and transparent. Notaries are also responsible for providing legal advice and ensuring that transactions are carried out voluntarily and in accordance with applicable regulations. However, the notarial profession faces various ethical challenges, such as conflicts of interest and breaches of confidentiality, which can undermine the credibility of transactions and public trust in the profession. Ethical violations can result in financial losses for the parties involved and damage the reputation of the legal system as a whole. Therefore, it is essential for notaries to maintain independence, integrity, and professionalism in carrying out their duties to ensure the creation of legal certainty that supports smooth, valid, and trustworthy business transactions.